A blended rational emotive occupational health coaching for job-stress among teachers of children with special education needs - Francisca Chinwendu Okeke (Elsevier, 2021)
Background/objectives: Heightened stress tends to undermine both teachers' efficacy and students' outcomes. Managing job stress in teachers of children with special education needs is continually recommended due to the increased demands for the teachers to adapt curriculum content, learning materials and learning environments for learning. This study investigated the efficacy of blended Rational Emotive Occupational Health Coaching in reducing occupational stress among teachers of children with special needs in Abia State, Nigeria. Method: The current study adopted a group-randomized waitlist control trial design with pretest, post-test and follow-up assessments. Participants (N = 83) included teachers of children with special education needs in inclusive and specialized schools. The bREOHC group was exposed to intersession face-to-face and online REOC program weekly for twelve (12) weeks. Data were collected using Single Item Stress Questionnaire (SISQ), Teachers' Stress Inventory and Participants' Satisfaction questionnaire (PSQ). Data collected at baseline; post-test as well as follow-up 1 and 2 evaluations were analyzed using mean, standard deviation, t-test statistics, repeated measures ANOVA and bar charts. Results: Results revealed that the mean perceived stress, stress symptoms and the total teachers' stress score of the bREOHC group at post-test and follow up assessments reduced significantly, compared to the waitlisted group. Participants also reported high level of satisfaction with the therapy and procedures. Conclusion: From the findings of this study, we conclude that blended REOHC is efficacious in occupational stress management among teachers of children with special education needs.